The role of RNA N6-methyladenosine methyltransferase in cancers - Jiali Huang; Zhenyao Chen; Xin Chen; Jun Chen; Zhixiang Cheng; Zhaoxia Wang (Elsevier, 2021)
Modification of eukaryotic RNA by methylation of adenosine residues to generate N6-methyladenosine (m6A) is a highly prevalent process. m6A is dynamically regulated during cell metabolism and embryo development, and it is mainly involved in various aspects of RNA metabolism, including RNA splicing, processing, transport from the nucleus, translation, and degradation. Accumulating evidence shows that dynamic changes to m6A are closely related to the occurrence and development of cancer and that methyltransferases, as key elements in the dynamic regulation of m6A, play a crucial role in these processes. Therefore, in this review, we describe the role of methyltransferases as m6A writers in cancer and summarize their potential molecular mechanisms of action.